2023
DOI: 10.1186/s13100-023-00308-3
|View full text |Cite
|
Sign up to set email alerts
|

An intronic LINE-1 regulates IFNAR1 expression in human immune cells

Carmen A. Buttler,
Daniel Ramirez,
Robin D. Dowell
et al.

Abstract: Background Despite their origins as selfish parasitic sequences, some transposons in the human genome have been co-opted to serve as regulatory elements, contributing to the evolution of transcriptional networks. Most well-characterized examples of transposon-derived regulatory elements derive from endogenous retroviruses (ERVs), due to the intrinsic regulatory activity of proviral long terminal repeat regions. However, one subclass of transposable elements, the Long Interspersed Nuclear Elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…For example, one study suggested that intronic L1s are part of an important regulatory network maintaining T-cell quiescence [ 32 ]. This is consistent with the increasing appreciation for the importance of alternative splicing in immune regulation and cell death pathways [ 33 ] and with another pair of studies highlighting the importance of TE exonization and intronic TE co-option in interferon signaling [ 34 , 35 ]. Additionally, L1 RNA may be sufficient to induce an interferon response and alter cellular viability, even in the absence of transposition [ 36 , 37 ].…”
Section: Introductionsupporting
confidence: 88%
“…For example, one study suggested that intronic L1s are part of an important regulatory network maintaining T-cell quiescence [ 32 ]. This is consistent with the increasing appreciation for the importance of alternative splicing in immune regulation and cell death pathways [ 33 ] and with another pair of studies highlighting the importance of TE exonization and intronic TE co-option in interferon signaling [ 34 , 35 ]. Additionally, L1 RNA may be sufficient to induce an interferon response and alter cellular viability, even in the absence of transposition [ 36 , 37 ].…”
Section: Introductionsupporting
confidence: 88%
“…In humans, most of these co-opted regulatory elements are found within ERVs ( Chuong et al, 2016 ). However, non-LTR elements, such as L1M2a, were also shown to act as IFN-inducible enhancers ( Buttler et al, 2023 ). In contrast, in mice, B2 elements are the predominant source of these regulatory sequences ( Horton et al, 2023 ).…”
Section: Insights Into Transposable Elementsmentioning
confidence: 99%